2011
DOI: 10.1021/ja204233q
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Design of Porous Coordination Polymer Crystals by Coordination Modulation

Abstract: The design of crystal morphology, or exposed crystal facets, has enabled the development (e.g., catalytic activities, material attributes, and oriented film formation) of porous coordination polymers (PCPs) without changing material compositions. However, because crystal growth mechanisms are not fully understood, control of crystal morphology still remains challenging. Herein, we report the morphology design of [Cu(3)(btc)(2)](n) (btc = benzene-1,3,5-tricarboxylate) by the coordination modulation method (modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
304
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 409 publications
(315 citation statements)
references
References 70 publications
9
304
0
2
Order By: Relevance
“…20,21 However, the application of this method is, to date, limited to a framework system that intrinsically has a rather fast nucleation process. 2225 This is because the coordination modulation tends to decelerate the nucleation kinetics and helps to grow crystals larger.…”
Section: 18mentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 However, the application of this method is, to date, limited to a framework system that intrinsically has a rather fast nucleation process. 2225 This is because the coordination modulation tends to decelerate the nucleation kinetics and helps to grow crystals larger.…”
Section: 18mentioning
confidence: 99%
“…19 This rather coordination chemistry approach allows us to control both crystallization kinetics and thermodynamics by simply altering the concentration of modulators, which affords the control of crystal size and morphology in nano and meso scales, and to synthesize highly crystalline materials. 20,21 However, the application of this method is, to date, limited to a framework system that intrinsically has a rather fast nucleation process. 2225 This is because the coordination modulation tends to decelerate the nucleation kinetics and helps to grow crystals larger.…”
mentioning
confidence: 99%
“…[ 24 ] It has been that demonstrated that the geometric shape of a MOF is determined by the relative growth rates of each crystal facet, which are inversely proportional to the attachment energy of a defi ned growth unit on crystal facets, similar to atoms as units in metal nanocrystal growth. [ 25 ] Therefore, adjusting the growth rates of different crystal facets should be applicable for the growth of low-dimensional MOFs, e.g., using growth-blocking agents to inhibit the crystal growth in certain directions. [ 26,27 ] As one of the most important MOFs, HKUST-1 (i.e., Cu 3 (BTC) 2 (H 2 O) 3 , where the parent molecule of BTC 3− linker is H 3 BTC (1,3,5-benzenetricarboxylic acid, see Scheme 1 )), has been widely studied since it was fi rst reported in 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments to understand the crystallization processes of MOFs will enable us to partially control their sizes and shapes by controlling the recrystallization conditions. [19] This prompted us to fabricate a polyhedral polymer network in a wide range of sizes using a cross-linking reaction inside the MOFs. In a previous report, we demonstrated the formation of a polymer gel from a MOF by cross-linking of the organic linkers in the crystalline state of the MOF using an in situ click reaction of the azidemodified MOF, with external multifunctional cross-linkers with four acetylene moieties.…”
mentioning
confidence: 99%